Developments in amphibian captive breeding and reintroduction programs. Issue 2 (2nd December 2015) - Harding, Gemma; Griffiths, Richard A.; Pavajeau, Lissette
Abstract: Captive breeding and reintroduction remain high profile but controversial conservation interventions. It is important to understand how such programs develop and respond to strategic conservation initiatives. We analyzed the contribution to conservation made by amphibian captive breeding and reintroduction since the launch of the International Union for Conservation of Nature (IUCN) Amphibian Conservation Action Plan (ACAP) in 2007. We assembled data on amphibian captive breeding and reintroduction from a variety of sources including the Amphibian Ark database and the IUCN Red List. We also carried out systematic searches of Web of Science, JSTOR, and Google Scholar for relevant literature. Relative to data collected from 1966 to 2006, the number of species involved in captive breeding and reintroduction projects increased by 57% in the 7 years since release of the ACAP. However, there have been relatively few new reintroductions over this period; most programs have focused on securing captive‐assurance populations (i.e., species taken into captivity as a precaution against extinctions in the wild) and conservation‐related research. There has been a shift to a broader representation of frogs, salamanders, and caecilians within programs and an increasing emphasis on threatened species. There has been a relative increase of species in programs from Central and South America and the Caribbean, where amphibian biodiversity is high. About half of the programs involve zoos and aquaria with a similar proportion represented in specialist facilities run by governmental or nongovernmental agencies. Despite successful reintroduction often being regarded as the ultimate milestone for such programs, the irreversibility of many current threats to amphibians may make this an impractical goal. Instead, research on captive assurance populations may be needed to develop imaginative solutions to enable amphibians to survive alongside current, emerging, and future threats.